Entrepreneurial Values in Accounting Education Students at Universitas Muhammadiyah Surakarta - Suranto, S; Rahayu, Mutiara Silvy (Proceedings International Conference on Education Innovation and Social Science, 2022)
In facing the dynamics of progress in the industrial revolution era, entrepreneurial values become an essential part that university students must own. For this reason, this study aims to describe the entrepreneurial values of university students. This qualitative research used an ethnographic design. Data collection was carried out by interview, observation, and documentation. Respondents comprised students from the accounting education study program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, totaling 12 people. The data validity employed the source and method triangulation analyses, whereas the analysis technique utilized data reduction, data display, and drawing conclusions. The results uncovered six entrepreneurial values in accounting education students. 1) Students had self-confidence, seen from their confidence level in their abilities. 2) Students were highly responsible for the tasks given and were task and result oriented. 3) Students were brave and could take risks and anticipate risks that might come at any time. 4) Students had a foresight regarding business opportunities. 5) Students had a leadership spirit and could establish good communication. Also, 6) students could think creatively and innovatively in seeing new opportunities.